Evidence for Conical Magnetic Structure in M-Type BaFe12O19 Hexaferrite: A Combined Single-Crystal X-ray Magnetic Circular Dichroism and Neutron Diffraction Study - Kumar K.; Mishra S.K.; Singh S.; Baev I.; Martins M.; Orlandi F.; Manuel P.; Pandey D. (My University, 2025)
The magnetic ground state of BaFe12O19 (BFO) is investigated using X-ray absorption spectra (XAS), X-ray magnetic circular dichroism (XMCD), and neutron diffraction studies at 1.2 and 1.5 K, respectively. The XMCD measurements on single-crystals of BFO in grazing-incidence geometry reveal canting of the spins away from the c-axis of the hexagonal unit cell. Single-crystal neutron diffraction studies reveal magnetic satellite peaks along the 00l reciprocal lattice row around the forbidden l = 2n ± 1 positions confirming the conical-type magnetic structure in the ground state of BFO. The observation of the conical magnetic structure of BFO opens the possibility of type-II multiferroicity in undoped BFO. © 2021 Wiley-VCH GmbH